Binuclear Copper(I) Complexes for Near‐Infrared Light‐Emitting Electrochemical Cells - Jouaiti, Abdelaziz; Ballerini, Lavinia; Shen, Hsiang‐Ling; Viel, Ronan; Polo, Federico; Kyritsakas, Nathalie; Haacke, Stefan; Huang, Yu‐Ting; Lu, Chin‐Wei; Gourlaouen, Christophe; Su, Hai‐Ching; Mauro, Matteo (Angewandte Chemie, 2023)
Two binuclear heteroleptic Cu I complexes, namely Cu−NIR1 and Cu−NIR2, bearing rigid chelating diphosphines and π‐conjugated 2,5‐di(pyridin‐2‐yl)thiazolo[5,4‐ d ]thiazole as the bis ‐bidentate ligand are presented. The proposed dinuclearization strategy yields a large bathochromic shift of the emission when compared to the mononuclear counterparts (M1–M2) and enables shifting luminescence into the near‐infrared (NIR) region in both solution and solid state, showing emission maximum at ca. 750 and 712 nm, respectively. The radiative process is assigned to an excited state with triplet metal‐to‐ligand charge transfer ( 3 MLCT) character as demonstrated by in‐depth photophysical and computational investigation. Noteworthy, X‐ray analysis of the binuclear complexes unravels two interligand π–π‐stacking interactions yielding a doubly locked structure that disfavours flattening of the tetrahedral coordination around the Cu I centre in the excited state and maintain enhanced NIR luminescence. No such interaction is present in M1–M2. These findings prompt the successful use of Cu−NIR1 and Cu−NIR2 in NIR light‐emitting electrochemical cells (LECs), which display electroluminescence maximum up to 756 nm and peak external quantum efficiency (EQE) of 0.43 %. Their suitability for the fabrication of white‐emitting LECs is also demonstrated. To the best of our knowledge, these are the first examples of NIR electroluminescent devices based on earth‐abundant Cu I emitters.